Pelatihan Pemasaran E-Commerce Di SMK Saraswati 2 Denpasar - I Gusti Ngurah Satria Wijaya; Ketut Gus Oka Ciptahadi; Ni Putu Meina Ayuningsih (STMIK Royal, 2023)
Abstract: To actualize the vision and mission of the Saraswati 2 Vocational High School (SMK) Denpasar, namely to develop and improve high-quality human resources and provide public services in the form of information on ICT-based school activities, formed with the existence of a study program namely Computer Engineering & Informatics (Multimedia). Obstacles and problems currently encountered by the Computer and Informatics Engineering (Multimedia) study program are the lack of marketing training for photo and video products, especially e-commerce, among SMK students in order to realize the school's vision of forming independent graduates. The solution to the problem provided by the implementation of this service is to hold an e-commerce marketing workshop. The procedure or technique for implementing this community service is first, socialization activities, the main activities in the form of training, and monitoring and evaluation. The output of this service is that the process of e-commerce marketing training activities is carried out well and smoothly. Participants were happy and excited in participating in the training and easily understood the training material as indicated by the increase in scores from the pretest and posttest. Keywords: training; marketing; e-commerce Abstrak: Untuk merealisasikan visi dan misi Sekolah Menengah Kejuruan (SMK) Saraswati 2 Denpasar yaitu mengembangkan dan meningkatkan sumber daya manusia yang berkualitas tinggi dan memberikan layanan publik berupa informasi kegiatan di sekolah yang berbasis ICT, dibentuk dengan adanya program studi yaitu Teknik Komputer & Informatika (Multimedia). Kendala dan masalah yang saat ini ditemui oleh program studi Teknik Komputer dan Informatika (Multimedia) ini adalah masih minimnya pelatihan pemasaran untuk produk foto dan video khususnya e-commerce di siswa-siswa SMK guna merealisasikan visi sekolah dalam membentuk tamatan yang mandiri. Pemecahan masalah yang diberikan dari pelaksanaan pengabdian ini adalah mengadakan workshop pemasaran e-commerce. Tata cara atau teknik pelaksanaan pengabdian ini adalah pertama, kegiatan sosialisasi, kegiatan utama berupa pelatihan, dan monev. Output dari pengabdian ini adalah proses kegiatan pelatihan pemasaran e-commerce terlaksana dengan baik dan lancar. Peserta senang dan gembira dalam mengikuti pelatihan serta dengan mudah memahami materi pelatihan ditunjukkan dengan kenaikan nilai dari pretest dan postest.Kata kunci: pelatihan; pemasaran; e-commerce